People participation in Torbat-Heydarieh local government, Iran - Mohammadi, Seyed Hamid (2012)
The main purpose of the study is to investigate the process of people’s participation in Torbat-Heydarieh local government. Poor people’s participation in local government has been identified as a barrier to the development of good governance. This research via survey and interviews conducted illustrated that there are several factors and limitations contributing to the success of people’s participation in the local government activities. By highlighting these factors and limitations, the researcher’s goal is to mobilize research and policy efforts to overcome those limitations and to enhance the level of people participation in local government to promote good governance. It is acknowledged that local people play an important role in local decision making processes. The participation of local people in the decision making processes will empower them and this is a big step towards good governance. This study employed both quantitative and qualitative approaches. Questionnaire survey was used to identify the level of public participation and to examine the relationships between citizen perception towards participation, citizen attitude towards local government, civic engagement, and the characteristics of respondents with levels of people participation. Descriptive Statistics, Correlations, T-test, and One-way Anova were also performed to complete the data set. The study also employed qualitative interviews to identify the conflicts which arise over perceptions towards participation between the local people and members of the local government, as well as to determine the barriers of participation. The findings showed that the level of people participation in local government of Torbat-Heydarieh, Iran, is at non-participation level. This means that the people do not really participate in the decision making process. At this level of participation, it shows clearly that good governance will not be achieved in Torbat-Heydarieh. Several factors have contributed towards this non participation which include lack of knowledge and participatory skills among members of local government, lack of opportunity to participate and negative view towards local government among local people. This study also investigated the people’s perception towards participation and its relationship with level of participation. Based on findings of this study, although, the descriptive findings showed positive perception of respondents toward participation in local government but there was no significant relationship between perception and levels of participation. The study also investigated the people’s attitude towards local government and its relationship with level of participation. The result showed that level of non-participation has a negative relationship with attitude however the levels of tokenism and citizenpower had positive relationship with attitude towards local government. The T-test result showed that there is significant difference between male and female regarding their participation in levels of participation. One-way anova result also showed that participation of respondents are different based on their education background and types of their occupation. The findings of this study have important implications for developing people’s participation in Torbat- Heydarieh local government, particularly in the decision making process. The findings of this study contribute to the body of literature concerning people participation and good governance. The information gathered from this study will enable members of the local government to increase their capacity in terms of their attitude, accountability, awareness and to be more creative opening up new channels of communication and avenues for the local people to participate.. On the other hand, the local people will also have to increase their capacity and be more aware of the importance and benefits of participation and the opportunities to make a difference. The commitment and working together of both parties will enhance public participation and hence promote good governance.